Inefficient and unique processing of social–emotional interference in school-aged children with high-functioning autism spectrum disorder - Chen, Qing-Xin; Chen, Qi; Zhai, Kun; Chen, Hui-Ting; Wu, Yu-Lan; Liu, Jin-Ming; Jin, Yu (Frontiers in Psychiatry, 2024)
Introduction Interest is growing in investigating the ability of children with autism spectrum disorder (ASD) to process social information under conflicting and complex environments. However, few studies have employed objective behavioral measures to directly explore the underlying profile of social–emotional interference control. Methods In the current study, 53 children with ASD and 53 typically developing (TD) control, aged 6–12 years, completed a set of modified flanker tasks involving arrows, schematic faces, same real faces (with facial interference by the same person), and different real faces (with facial interference by different people), respectively. Response time in incongruent (RTInc) and congruent conditions (RTCon), percentage of errors in incongruent (%ErrorInc) and congruent conditions (%ErrorCon), and flanker effect calculated by ΔRT = (RTInc − RTCon)/RTCon and Δ%Error = %ErrorInc − %ErrorCon were used as outcome metrics. Results We obtained three major results: (1) the ASD group had longer RTInc and RTCon compared to the TD group in the arrow, schematic-face, and same real-face tasks; (2) compared with the performance in the arrow flanker task, both groups exhibited longer RTs and reduced ΔRTs in the same real-face task; however, in the schematic-face task, longer RT and reduced ΔRT were exhibited in the TD group, but not in the ASD group; and (3) in the different real-face task, ASD group had higher %Error than the TD group, and %Error was negatively correlated with RT only in the ASD group. Conclusion The current study delineates the inefficient processing of social–emotional interference in school-aged children with ASD and further suggests that these children might adopt a relatively optimized strategy like symbolization when dealing with emotional conflict. However, such compensatory cognitive strategies may be exhausted along with the increase in information load. These findings provide new perspectives of considering the difference more than difficulty in the cognitive profile of ASD, which will benefit the development of targeted behavioral interventions.